2024
DOI: 10.1186/s12939-024-02146-y
|View full text |Cite
|
Sign up to set email alerts
|

Does a new case-based payment system promote the construction of the ordered health delivery system? Evidence from a pilot city in China

Huanyu Shi,
Zhichao Cheng,
Zhichao Liu
et al.

Abstract: Background The construction of the ordered health delivery system in China aims to enhance equity and optimize the efficient use of medical resources by rationally allocating patients to different levels of medical institutions based on the severity of their condition. However, superior hospitals have been overcrowded, and primary healthcare facilities have been underutilized in recent years. China has developed a new case-based payment method called “Diagnostic Intervention Package” (DIP). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Guangzhou City saw short-term success slowing spending growth [ 34 ], while Chengdu City witnessed decreased average expenditure per hospital admission increase and improved medical quality post-reform [ 35 ]. One research in Taian City suggested utilization decreased at primary hospitals with less efficient resource use [ 36 ]. The DIP’s role remains unclear due to inconsistent evidence.…”
Section: Introductionmentioning
confidence: 99%
“…Guangzhou City saw short-term success slowing spending growth [ 34 ], while Chengdu City witnessed decreased average expenditure per hospital admission increase and improved medical quality post-reform [ 35 ]. One research in Taian City suggested utilization decreased at primary hospitals with less efficient resource use [ 36 ]. The DIP’s role remains unclear due to inconsistent evidence.…”
Section: Introductionmentioning
confidence: 99%